Factores Relevantes De Competitividad En Pymes - Amadeo Segura Hernández (European Scientific Journal, ESJ, 2018)
Competitiveness in all areas has increased with the opening of trade worldwide. This resulted to greater pressure on entities that have lags compared to others that are more prepared and which are better located internationally. In this context, small and medium-sized enterprises (SMEs) show lower levels of competitiveness than the large industry. This occurs most especially when they are located in developing countries, given the holistic nature of competitiveness. This paper focuses on identifying the relevant factors of competitiveness of SMEs. During the bibliographic research, networks, finances, innovation, and information systems were identified as recurrent preponderant factors in the four levels of systemic competitiveness: micro, meso, macro, and meta. This article shows the result of the first stage of the research, and is structured with concurrent triangulation design to perform cross validation of quantitative and qualitative aspects. The study was performed using a non-probabilistic sampling and with systemic representation through personalized interviews of different people from different groups involved in the system of which the SME’s of the State of Puebla, Mexico, are partly related to the automotive and auto parts sector. The four factors were confirmed in this research stage and, at the same time, five other relevant factors were also recognized: knowledge, culture, specialization, diversification, and institutionalization. The identification of the predominant factors of competitiveness offers the possibility of developing them holistically by the various related actors that provide the enabling environment for the strengthening of SMEs.